(untitled) (Perner’s Contacts, 2009)
Manufacturers of vehicles implement innovative technologies which help people to drive safely and avoid collisions. New technologies bring opportunities for road safety. Increasing of vehicle safety is key strategy in reduction number of accidents on national and international level and in achieving higher road safety. It is clear that development and application of intelligent transport systems should not be implemented late. European Union, its member states and representatives of the automotive industry integrated their approach to improve the effectiveness of these new security technologies.